(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Valerya A. Trofimova, Larisa S. Abrosimova (Southern Federal University, Rostov-on-Don, Russian Federation) This article analyzes the phenomenon of verbal strategies in the political discourse. The authors consider the ways of language self-realization strategy on the material of pre-election speeches by Hillary Clinton. Within the study it has been revealed the most typical means of linguistic expression, as well as the method of operation in question. The performance peculiarity of the presidential candidate speech, as it has been noted, is her ability to combine the expressive potential of syntactic and lexical and grammatical means. Key words: strategy of self-presentation, emotional impact, expressive means. DOI: 10.18522/1995-0640-2016-4-85-92